Tantangan dan Solusi Pembelajaran Agama Islam di Sekolah Inklusi - Dita Dzata Mirrota (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2024)
This research aims to examine the challenges, the condition of religious material understanding, and effective strategies and methods of religious education for students at SMPLB Shafa Mojokerto. The study employs a qualitative approach with a case study method. Data collection is conducted through interviews, observations, and documentation of the school principal, three teachers, and three students. The research findings indicate that the main challenges faced by religious teachers are the disparity in students' understanding levels, resource limitations, and the difficulty of effective communication with students with special needs. Nevertheless, the maximum efforts of teachers and school support manage to overcome these various obstacles. Overall, the students' understanding and acceptance of religious material are relatively good, although some students still encounter difficulties in grasping specific topics. Effective learning strategies include implementing an inclusive approach, active and contextual learning, optimizing the role of parents and the family environment, and emphasizing the internalization of religious values in shaping students' character. Recommendations include improving the availability of learning resources and support facilities, providing teacher training, and continuously evaluating and refining religious education methods to adapt to students' evolving needs.